(untitled) (Global Scientific Review, 2023)
In this article, the history of the origin of administrative justice, its specific features are scientifically analyzed. Also, theoretical and practical researches were conducted. In addition, the stages of development of administrative justice and its role and importance in administrative law are explained in detail. In addition, scientific researches and conclusions of foreign and national scientists regarding the role of administrative justice in solving public legal disputes have been analyzed and studied.